Photovoltaic power generation - Pulfrey, David L. (Van Nostrand Reinhold Company, 1978)
Producing electricity from the sun using photovoltaic (PV) systems has become a major industry worldwide. But designing, installing and maintaining such systems requires knowledge and training, and there have been few easily accessible, comprehensive guides to the subject.